Clinical profile and outcome of acute kidney injury in intensive care unit of a teaching hospital - Shrestha, Bidhan; Shrestha, Sabita; Shrestha, Rakshya; Paudel, Pramod; Dhakal, Hari Krishna; Shah, Mukesh Ranjan; Deep, Suresh Kumar; Sedhai, Sabina (Journal of Chitwan Medical College, 2018)
Objectives: Acute kidney injury is one of the most common cause of hospitalization in developing countries. Causes of AKI are multifactorial. Most of AKI are community acquired. The objective of the study was to identify the clinical profile and outcome of acute kidney disease. Subject and Methodology: 30 patients from Chitwan Medical College outpatient clinic were included in the study from November 2014 to April 2015. A brief history and clinical examinations were taken from all patients along with laboratory tests for Renal function tests, urine output, metabolic parameters and hematological profile. Results: 19 males (63.3% and 11 females (36.7%) were studied. The main causes for AKI were sepsis (46.6%) followed by hepatic causes (16.6%), gastroenteritis (10%) and others (10.2%). Out of 30 patients, 19 recovered (63.3%) and were discharged and 11(36.7%) died. Most of the deaths were in injury (37.5%) and failure (42.8%) stages of RIFLE criteria. Out of 19 recovered 16(84.21%) patients did not need any renal replacement therapy whereas 3(15.8%) patients had to undergo hemodialysis. Conclusion: Early identification of kidney injury may lead to lesser renal replacement therapy and better prognosis. However late presentations of AKI have higher hospital mortality rate.